JOB SATISFACTION THROUGH WORK-LIFE BALANCE WITH THE ROLE OF INCLUSIVITY AS AN INDEPENDENT VARIABLE - Amrullah; Andi Isma; Nurmita; Abd. Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the direct and indirect influence of the variables of Inclusivity, Work Life Balance, and Job Satisfaction. Work Life Balance as an intervening variable. The method used is a quantitative descriptive approach with a purposive sampling technique, namely sampling with criteria that have been determined by the researcher. The data collection method uses a questionnaire with interval scale measurements and uses 120 respondents as a sample. For data analysis, model tests were used using the Smart PLS analysis tool. The results of this study show that inclusivity has a significant influence on work-life balance and job satisfaction directly, and it is found that work-life balance has a significant role in mediating between inclusivity and job satisfaction